Evaluation of sequential applications of quizalofop-P-ethyl and florpyrauxifen-benzyl in acetyl CoA carboxylase-resistant rice. (19th April 2021) - Sanders, Tameka L.; Bond, Jason A.; Lawrence, Benjamin H.; Golden, Bobby R.; Allen, Thomas W.; Bararpour, Taghi
Abstract: Information on performance of sequential treatments of quizalofop-P-ethyl with florpyrauxifen-benzyl on rice is lacking. Field studies were conducted in 2017 and 2018 in Stoneville, MS, to evaluate sequential timings of quizalofop-P-ethyl with florpyrauxifen-benzyl included in preflood treatments of rice. Quizalofop-P-ethyl treatments were no quizalofop-P-ethyl; sequential applications of quizalofop-P-ethyl at 120 g ha −1 followed by (fb) 120 g ai ha −1 applied to rice in the 2- to 3-leaf (EPOST) fb the 4-leaf to 1-tiller (LPOST) growth stages or LPOST fb 10 d after flooding (PTFLD); quizalofop-P-ethyl at 100 g ha −1 fb 139 g ha −1 EPOST fb LPOST or LPOST fb PTFLD; quizalofop-P-ethyl at 139 g ha −1 fb 100 g ha −1 EPOST fb LPOST and LPOST fb PTFLD; and quizalofop-P-ethyl at 85 g ha −1 fb 77 g ha −1 fb 77 g ha −1 EPOST fb LPOST fb PTFLD. Quizalofop-P-ethyl was applied alone and in mixture with florpyrauxifen-benzyl at 29 g ai ha −1 LPOST. Visible rice injury 14 d after PTFLD (DA-PTFLD) was no more than 3%. Visible control of volunteer rice ('CL151' and 'Rex') 7 DA-PTFLD was similar and at least 95% for each quizalofop-P-ethyl treatment. Barnyardgrass control with quizalofop-P-ethyl at 120 fb 120 g ha −1 LPOST fb PTFLD was greater (88%) in mixture with florpyrauxifen-benzyl. The addition of florpyrauxifen-benzyl to quizalofop-P-ethyl increased rough rice yield when quizalofop-P-ethyl was applied at 100 g ha −1 fb 139 g ha −1 EPOST fb LPOST. Sequential applications of quizalofop-P-ethyl at 120 g ha −1 fb 120 g ha −1 EPOST fb LPOST, 100 g ha −1 fb 139 g ha −1 EPOST fb LPOST, or 139 g ha −1 fb 100 g ha −1 EPOST fb LPOST controlled grass weed species. The addition of florpyrauxifen-benzyl was not beneficial for grass weed control. However, because quizalofop-P-ethyl does not control broadleaf weeds, florpyrauxifen-benzyl could provide broad-spectrum weed control in acetyl coenzyme A carboxylase–resistant rice.